PERBANDINGAN SKOR HARKIT DENGAN SKOR SOCIETY OF THORACIC SURGEONS (STS) DALAM MEMPREDIKSI TINGKAT MORTALITAS PASIEN PASKA OPERASI KATUP DI RUMAH SAKIT UMUM PUSAT HAJI ADAM MALIK MEDAN - Lubis, Ainil Wardah; Sitepu, Andika; Intan, Tengku Kemala; Tanjung, Ika Citra Dewi (The Indonesian Heart Association, 2024)
Background: Valvular heart disease is a major contributor to increased mortality. The HARKIT score has been validated to predict mortality after specific valve surgery and the STS score to predict mortality rates in patients after cardiac surgery. Haji Adam Malik General Hospital Medan has never used the HARKIT score and the STS score to predict mortality in patients with post valve surgery. Methods: A cross-sectional study from January 2022-April 2023 at Haji Adam Malik General Hospital Medan. The data used is obtained from patient medical record who had heart valve surgery. The data were analyzed with descriptive statistics and presented the form of frequency distribution. Comparison of the HARKIT score with the STS score to predict mortality rates were analyzed using chi-square test. Results: Among 63 patients who underwent valve surgery, 8 patients died after surgery. The HARKIT score system has good analytical power and very strong discriminant (H-L test P=0.646; AUC=0.916; 95% CI=0.794-1.000), while the STS score has poor analytical power (H-L test P=0.002) but has moderate discriminant (AUC=0.798; 95% CI=0.632-0.964). Conclusion: The HARKIT score is more accurate than the STS score in predicting the mortality rate of post-valve surgery patients at Haji Adam Malik General Hospital Medan.